Comparative Study of the Synthesis of sub‐10 nm Carbon‐Supported Gold Nanoparticles and their Suitability for Methanol Electrooxidation in Alkaline Media. Issue 6 (5th May 2022) - Dieterich, Emil; Kinkelin, Simon‐Johannes; Bron, Michael
Abstract: Gold nanoparticles where synthesized and supported on carbon, or directly synthesized on carbon according to five different methods reported in literature, aiming at particles<10 nm. Characterization was done with transmission electron microscopy and thermogravimetric analysis. Although all syntheses yielded particles with an average diameter<10 nm, the formation of few very large particles, where a relatively large amount of Au is buried, as well as loss during the supporting procedure led to the exclusion of four of the five tested methods for further studies. The most promising AuNPs supported on carbon where tested for the methanol electrooxidation (MEO) in alkaline media. Four different Au‐loadings where realized, and supporting led to moderate particle growth depending on the loading. To compare MEO activity of the samples with different Au‐loadings a conversion factor was developed where the MEO activity can be compared in terms of NP size and Au‐loading. Abstract : Sub‐10 nm gold nanoparticles were synthesized according to various reported procedures and compared with respect to particle size, size distribution and gold loss. The most promising nanoparticles where supported on carbon and tested for the MeOH electrooxidation and compared in terms of Au‐loading and particle size.